External conflicts, local threats: tackling radicalisation the Singapore way - Mohamed Bin Ali (2025)
The actions taken by Singapore’s Internal Security Department against three individuals recently highlight the worrying trend of radicalisation. While external conflicts, such as the Israel-Hamas war, often serve as catalysts, radicalisation is a multifaceted phenomenon influenced by a combination of personal, social, and ideological factors. Singapore has developed unique and effective counter-radicalisation measures to deal with this persistent threat.